The Simultaneous Regional Elections of 2024 and the Leadership of Islamic Clerics in Palembang - Ahmad Fauzan, Masagus (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
The Simultaneous Regional Elections (Pilkada) in 2024 in Palembang are of significant concern in the context of Indonesian democracy. This study discusses the role of religious leaders (ulama) in the 2024 Simultaneous Regional Elections and its implications for leadership in Palembang. As a democratic country, general elections serve as a primary indicator in evaluating the democratization process. The role of ulama in local politics is significant, not only as spiritual leaders but also as social and political movers. The interaction between religion and politics poses challenges related to balancing religious values and democratic principles. Nonetheless, elections, including Pilkada, are considered crucial instruments in building democracy, albeit still facing challenges such as money politics and the use of religious identities for political purposes. In this context, increased oversight of unethical political practices, strengthening regulations related to campaign financing, and enhancing public participation in the political process are necessary to ensure a healthy and sustainable democratization process in Indonesia. Therefore, the 2024 Simultaneous Regional Elections in Palembang represent a crucial moment to strengthen democracy and enhance public participation in the political process, with continuous improvement and enhancement measures needed to maintain the integrity and sustainability of democracy in Indonesia.